(untitled) (Eurasian Journal of Ecology, 2018)
Environmental pollution with oil and petroleum products leads to a decrease in animal biodiversity and human diseases. Due to the intense pollution of Kazakhstan’s water bodies located on the territory of oil producing regions, the purpose of this study was to study the effect of different concentrations of oil on the growth and development of the green toad (Bufo viridis). This species of anuran amphibians is widespread in Kazakhstan, which is especially important given the aridity of the lands of the oil-producing regions. A chronic exposure to the concentrations of oil hydrocarbons found in the water of the reservoirs of the Aktobe, Atyrau and Mangistau regions on the tadpoles of the green toad (Bufo viridis) was carried out The results of the study revealed suppression of growth (size and weight) and a developmental delay in tadpoles from experimental groups. To determine the reasons for the slowdown in growth and development, the content of lipid peroxidation products (LHO and MDA) and the activity of antioxidant defense enzymes in the liver of tadpoles of the green toad (Bufo viridis) were studied. It has been shown that the production of LHO and MDA increases after exposure of the tadpoles to oil hydrocarbons, while the activity of antioxidant enzymes, on the contrary, decreases, which indicates enhanced oxidative stress in the liver of the treated tadpoles. Thus, exposure to oil hydrocarbons in concentrations found in the water bodies of the oil producing regions of Kazakhstan suppresses the growth and development of the green toad (Bufo viridis), one of the reasons of which is the increase of oxidative stress. Key words: water soluble fraction of oil, Bufo viridis, growth, development, oxidative stress, lipid peroxidation, antioxidant enzymes.